GAMBARAN BALITA STUNTING BERDASARKAN KARAKTERISTIK DEMOGRAFI IBU DI WILAYAH KERJA PUSKESMAS PUNDONG BANTUL YOGYAKARTA - suryati suryati; Supriyadi Supriyadi; Eka Oktavianto (Medika Respati : Jurnal Ilmiah Kesehatan, 2020)
Background: Stunting is still a children’s nutrition problem at this time. The percentage of cases of stunting children’s is increasing. Stunting can affect children in the long run, that is, disrupt health, education and productivity in the future. Maternal demographic factors are thought to be a factor that plays a role in the occurrence of stunting children.Purpose: provide an overview and discussion of stunting based on maternal demographic characteristics.Method: This research is a non-experimental research with an observational descriptive approach. Data was collected using a demographic characteristics questionnaire. The sample in this study was 90 stunting toddlers in the working area of the Pundong Community Health Center, Bantul, Yogyakarta. The sampling technique in this study uses simple random sampling. Data analysis uses percentage formulasResults: in stunting toddlers, the majority of maternal’s aged less than 30 years were 52 people (58%), the majority of maternal’s' education was low education (junior high school and elemtary school) which was 60 people (66%), the number of family members was more than 4 people were as many as 64 respondents (66.7%), the majority of mother who did not work were 52 people (57.8%), had incomes that were less than district minimum wage, which were 63 people (70%).Conclusion: there are several parental demographic factors that have a role in the occurrence of stunting under five, such as: maternal’s age, level of education, number of family members, employment status, and family income.